Shifting baselines of coral‐reef species composition from the Late Pleistocene to the present in the Florida Keys - Lauren T. Toth; Anastasios Stathakopoulos; Scarlette Hsia; David Weinstein (The Depositional Record)
Abstract The ongoing global‐scale reassembly of modern coral reefs is unprecedented compared with the observed stability of most late Quaternary reef assemblages. One notable exception is the marine isotope stage (MIS) 5e (ca 130–116 thousand years ago [ka]) reefs in the Florida Keys, where the ubiquitous shallow‐water coral, Acropora palmata, was near absent. Little is known, however, about reefs that grew during MIS5d–a (ca 116–74 ka), between MIS5e and the Holocene. It is therefore unclear whether Florida's unique MIS5e coral assemblages represent a geologically brief anomaly or a more persistent departure from the western Atlantic coral‐reef archetype. We addressed that question by reconstructing the composition of MIS5d–a reefs within 29 coral‐reef cores collected throughout the Florida Keys. We then compared the relative composition of corals during MIS5d–a to existing datasets from MIS5e, Holocene and modern (1996 and 2022) reefs to evaluate how far today's reef assemblages have diverged from geological baselines. We show that although the proportion of reef frameworks built by corals was remarkably consistent (ca 38%), species composition changed significantly through time. Acropora palmata was rare throughout MIS5, which we hypothesise was due to greater cold‐temperature stress in Florida's subtropical reefs compared with the more climatically stable tropics. In contrast, the massive reef‐building coral, Orbicella spp., was regionally dominant throughout the late Quaternary, but has become increasingly rare on modern reefs. By 2022, reefs in the Florida Keys were characterised by a truly novel coral assemblage dominated by Porites astreoides and Siderastrea siderea. In many ways, Florida's reefs defy the concept of a natural baseline; instead, their most persistent characteristic since the Late Pleistocene is their uniqueness. Yet, as reefs are increasingly subjected to unprecedented levels of environmental change, the exceptions to what was normal in the past could, paradoxically, provide the best geological analogues for the future.